2006
DOI: 10.1002/mas.20116
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic 18O‐labeling strategies for quantitative proteomics

Abstract: A number of proteomic techniques have been developed to quantify proteins in biological systems. This review focuses on the quantitative proteomic technique known as "proteolytic 18O-labeling." This technique utilizes a protease and H(2)18O to produce labeled peptides, with subsequent chromatographic and mass spectrometric analysis to identify and quantify (relative) the proteins from which the peptides originated. The technique determines the ratio of individual protein's expression level between two samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
210
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(214 citation statements)
references
References 62 publications
4
210
0
Order By: Relevance
“…Immobilized trypsin was used in both the digestion and labeling steps to prevent exchange of the 16 O and 18 O label that would occur if the labeled and unlabeled peptides were mixed in the presence of residual free protease. As previously described (40), the decoupling of the digestion and labeling procedures enabled us to carry out each step at its optimal pH (i.e. pH 8.0 and 6.0, respectively).…”
Section: Preparation Of Bacterial Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immobilized trypsin was used in both the digestion and labeling steps to prevent exchange of the 16 O and 18 O label that would occur if the labeled and unlabeled peptides were mixed in the presence of residual free protease. As previously described (40), the decoupling of the digestion and labeling procedures enabled us to carry out each step at its optimal pH (i.e. pH 8.0 and 6.0, respectively).…”
Section: Preparation Of Bacterial Expressionmentioning
confidence: 99%
“…pH 8.0 and 6.0, respectively). The labeling reaction occurred at an acidic pH of 6.0 and in an aqueous solution containing 25% (v/v) CH 3 CN because previous studies showed that the addition of organic solvents accelerates trypsin-catalyzed oxygen exchange (39,40). After adding phenylmethylsulfonylfluoride to inhibit the trypsin, the mixture was filtered using Amicon Ultra-0.5 ml centrifugal filters (molecular weight cutoff, 10 kDa), and the labeled and unlabeled peptides were recovered from the filtrate.…”
Section: Preparation Of Bacterial Expressionmentioning
confidence: 99%
“…Band 1 was from the top to 190 kDa, band 2 was from 190 to 75 kDa, band 3 was from 75 to 40 kDa, band 4 was from 40 to 30 kDa, and band 5 was from 30 kDa to the bottom. Resulting peptides from the CLRN1-interacting proteins and non-specifically bound proteins were labeled by 18 O and 16 O, respectively, as described previously (23,24), mixed in a 1:1 ratio, and desalted on a C18 column according to the manufacturer's manual. Mixed peptides were dissolved in 0.1% formic acid and analyzed by liquid chromatography-tandem mass spectrometry with an LTQ-Orbitrap mass spectrometer (Thermo Electron Corp., Bremen, Germany) (23).…”
Section: N48kmentioning
confidence: 99%
“…15 N or 18 O), thereby altering the mass of most or all proteins in one of the samples in a predictable fashion. These stable isotopes may be incorporated metabolically into (ideally) all proteins [7][8][9][10], in vivo, or a chemical reagent can be used to label the peptides/ proteins [11][12][13], in vitro. Examples of the former include the popular stable isotope labelling with amino acids in cell culture (SILAC) approach, where cells are cultured in a medium containing a heavy-amino acid, and compared to one containing the standard 'light' variant.…”
Section: Quantitative Proteomic Methodsmentioning
confidence: 99%